The role of sleep in Alzheimer’s disease: a mini review - Pathmanathan, Jay; Westover, M. Brandon; Sivakumaran, Sudhir; Donoghue, Jacob; Puryear, Corey B. (Frontiers in Neuroscience, 2025)
Sleep is a stereotyped and well-preserved series of neurophysiological states that are essential for overall health and brain functioning. Emerging research suggests that sleep disturbances are not only associated with but also causally contribute to neurodegenerative disease onset and progression. This mini-review examines some of the current knowledge and evidence for relationships between sleep abnormalities and Alzheimer’s disease within context of possible uses and limitations of sleep biomarkers for evaluation of Alzheimer’s disease. Understanding these relationships could lead to readily accessible and easily quantifiable biomarkers of Alzheimer’s dementia.